2007
DOI: 10.1074/jbc.m609597200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ubiquitin System Alterations on the Formation and Loss of a Yeast Prion

Abstract: ]. However, ubc4⌬ increases the proportion of the Hsp70 chaperone Ssa bound to Sup35, suggesting that misfolded Sup35 is either more abundant or more accessible to the chaperones in the absence of Ubc4. The proportion of [PSI ؉ ] cells containing large aggregated Sup35 structures is also increased by ubc4⌬. We propose that UPS alterations induce an adaptive response, resulting in accumulation of the large "aggresome"-like aggregates that promote de novo prion generation and prion recovery from the chaperone tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 58 publications
5
96
0
1
Order By: Relevance
“…Reducing ubiquitin (Ub) levels reduces the curing, while increasing Ub enhances it. 29,30 Sup35p is not ubiquitylated under either of these conditions, suggesting that Ub-mediated regulation or turnover of an unknown component is important for the curing process. The Hsp90 chaperone system, which serves as a post-translational regulator of many cellular processes, is also important for the curing mechanism.…”
Section: Hsp104mentioning
confidence: 94%
“…Reducing ubiquitin (Ub) levels reduces the curing, while increasing Ub enhances it. 29,30 Sup35p is not ubiquitylated under either of these conditions, suggesting that Ub-mediated regulation or turnover of an unknown component is important for the curing process. The Hsp90 chaperone system, which serves as a post-translational regulator of many cellular processes, is also important for the curing mechanism.…”
Section: Hsp104mentioning
confidence: 94%
“…The 34-residue repeat ("tetratricopeptide")-containing cochaperones, Sti1p and Cpr7p, that mediate Hsp70-Hsp90 interactions have also been found to be involved in prion propagation ( Jones et al 2004;Reidy and Masison 2010), as have nucleotide exchange factors for Hsp70s, namely Sse1p and Fes1p (Fan et al 2007;. In addition to molecular chaperones, cytoskeletal proteins, elements of the ubiquitin system, and other factors modulate prion propagation in S. cerevisiae (Bailleul et al 1999;Bailleul-Winslett et al 2000;Allen et al 2007;Kryndushkin et al 2008).…”
Section: T He [Ure3] Prion Is a Self-propagating Amyloid (A Bmentioning
confidence: 99%
“…Third, the steady-state size of SDS-resistant Sup35 aggregates increases in [PSI ϩ ] strains deficient in Hsp104, Hsp70, or Hsp70 cochaperones (Eaglestone et al, 2000;Wegrzyn et al, 2001;Cox et al, 2003;Kryndushkin et al, 2003;Jones et al, 2004;Song et al, 2005;Fan et al, 2007;Kryndushkin and Wickner, 2007;SatputeKrishnan et al, 2007;Sadlish et al, 2008), an observation that is completely opposed to our findings for NatA mutants ( Figure 5C). In addition to these factors, the ubiquitin-conjugating enzyme Ubc4 and the Hsp70 family members Ssb1 and Ssb2 are predicted or proven substrates for NatA (Huang et al, 1987;Polevoda et al, 1999), are modifiers of the [PSI ϩ ] prion cycle Allen et al, 2007), and have demonstrated synthetic interactions with NatA (Gautschi et al, 2003;Pan et al, 2006). Despite these intriguing connections, ⌬ubc4 and ⌬ssb1⌬ssb2 strains, unlike NatA null strains, display the [PSI ϩ ] nonsense suppression phenotype, indicating that they are unlikely to be the crucial NatA targets.…”
Section: Discussionmentioning
confidence: 99%